2013
DOI: 10.1097/der.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum 25-Hydroxyvitamin D Levels in Children with Atopic Dermatitis

Abstract: Patients with AD have lower serum vitamin D levels than normal. Vitamin D deficiency might be related to the severity of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 32 publications
6
26
4
1
Order By: Relevance
“…Also, in large population-based studies, it was observed that there is an increased likelihood of developing AD in individuals with either deficient or insufficient vitamin D levels [117,118]. Many observational studies including a meta-analysis have shown that the serum vitamin D level is lower in children and adults with AD compared to controls, and reported an association between vitamin D deficiency and risk of atopic eczema [119,120,121]. Also, the severity of AD was found to be negatively correlated with the vitamin D level, with moderate and severe AD groups having lower vitamin D levels compared to the mild AD group; this finding was supported by the use of objective tools, such as the SCORAD (Scoring Atopic Dermatitis) index, which was found to be inversely correlated with vitamin D levels in AD patients [120,121,122,123].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in large population-based studies, it was observed that there is an increased likelihood of developing AD in individuals with either deficient or insufficient vitamin D levels [117,118]. Many observational studies including a meta-analysis have shown that the serum vitamin D level is lower in children and adults with AD compared to controls, and reported an association between vitamin D deficiency and risk of atopic eczema [119,120,121]. Also, the severity of AD was found to be negatively correlated with the vitamin D level, with moderate and severe AD groups having lower vitamin D levels compared to the mild AD group; this finding was supported by the use of objective tools, such as the SCORAD (Scoring Atopic Dermatitis) index, which was found to be inversely correlated with vitamin D levels in AD patients [120,121,122,123].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Many observational studies including a meta-analysis have shown that the serum vitamin D level is lower in children and adults with AD compared to controls, and reported an association between vitamin D deficiency and risk of atopic eczema [119,120,121]. Also, the severity of AD was found to be negatively correlated with the vitamin D level, with moderate and severe AD groups having lower vitamin D levels compared to the mild AD group; this finding was supported by the use of objective tools, such as the SCORAD (Scoring Atopic Dermatitis) index, which was found to be inversely correlated with vitamin D levels in AD patients [120,121,122,123]. However, there are some contradictory reports, which suggest either no role of vitamin D or a positive association of vitamin D levels with the risk of developing AD [124,125].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…A potential link between VD and the development of allergic disease (the so-called “vitamin D hypothesis”) first emerged when higher rates of allergic disease were observed in people residing at higher latitudes, where VDD is common [11]. Although many clinical studies have found that 25(OH)D3 levels are significantly lower in patients with AD and negatively correlated with the severity of the disease [12-14], this view has remained controversial. Recently, additional studies have indicated that VD plays an important role in the pathogenesis of AD by regulating antimicrobial peptides, modulating immunity, and affecting skin barrier functions [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of such a finding in a large number of studies [5][6][7][17][18][19][20][21][22], confirms that the low level of calcidiol in such a disease is not a coincidence, and that calcidiol deficiency has a possible role in the pathogenesis of AD. The controversy in the serum level of calcidiol in AD patients is mainly viewed among adult AD patients, where several studies showed the non-significant alteration of calcidiol levels among patient and control groups [8,9].…”
Section: Groupmentioning
confidence: 53%